Integrated Problem and Decision Reporting as a Translator Training Tool - Daniel Gile (JoSTrans: The Journal of Specialised Translation)
Systematic reporting of problems and decisions encountered by translation students in their translation assignments has been used by the author for 25 years. Though it requires efforts from the students, it costs little in terms of information collection for the trainer and contributes much to both parties, including: readily available information about the students' problems, both individual and collective, information about their translation strategies, a means to raise their awareness of various components of the translation process and to promote best efforts towards maximum quality, a means to help them retain or boost their self-esteem even if the end-result is still mediocre, information about inter-subjective difficulties in source texts. The method has shown its didactic usefulness in a process-oriented training approach over the years, and, as a convenient type of retrospection, holds some promise for local and multi-centre empirical studies into translation expertise acquisition, especially now that electronic means allow relatively convenient processing of large amounts of information.